ON A POTENTIALLY RICH MILKFISH SEED COLLECTION GROUND NEAR MANDAPAM ALONG WITH THE METHODS OF COLLECTION AND TRANSPORATION - Dorairaj, K; Mohanraj, G; Gandhi, V; Raju, A; Rengaswamy, V S; Rodrigo, Joseph Xavier (Indian Journal of Fisheries, 2011)
A potential ground for milkfish seed collection has been located at Manoli Island in the Gulf of Mannar, where fry and fingerlings of the species congregate in large numbers in the tidal pools uncleI’ the dense shades of the mangrove bushes in April-May. The ecology of the ground, the methods and results of fry and fingerlings collection , handling, and packing and transportation are mentioned.